Emerging trends and effective strategies in STEM teacher professional development: A systematic review - Nadia Rehman; Xiao Huang; Amir Mahmood; Hafiz Muhammad Ihsan Zafeer; Nhelbourne Kalim Mohammad (Humanities & Social Sciences Communications)
Abstract Effective STEM education is closely linked to teacher professional development (TPD) quality. In response to the evolving demands of STEM education, the Chinese government has implemented numerous TPD programs across various cities and districts. This research systematically reviews 31 studies to identify the common objectives of STEM TPD projects, evaluate their impact on teachers’ competencies and instructional methods, and explore factors influencing project outcomes. The methodology involved extracting data and thematic analysis to provide qualitative insights into the effectiveness of TPD programs. The findings highlight a significant emphasis on interdisciplinary integration, innovative curriculum reform, and the development of technological proficiency among STEM teachers. Furthermore, the research identifies the need to extend training periods and provide targeted professional development to address specific regional challenges and the shortage of qualified STEM teachers. While there is a preference for interactive, in-person training sessions, a shift toward online modalities reflects changing professional development paradigms. Integrating STEM fields into educational settings fosters a more dynamic academic environment. However, the review also notes the predominance of interviews and surveys in data collection, underscoring the need for more diverse and robust empirical methodologies. Standardizing data collection and adopting comprehensive evaluation approaches are recommended to enhance the effectiveness of TPD programs. These insights provide a foundation for refining STEM TPD programs in China, calling for more empirical and holistic evaluations in future research.